Pain, Anxiety, and the Continuous Use of Opioids and Benzodiazepines in Trauma Intensive Care Unit Survivors: An Exploratory Study - Arroyo-Novoa, Carmen Mabel; Figueroa-Ramos, Milagros I.; Puntillo, Kathleen A. (Puerto Rico Health Sciences Journal, 2022)
Objective: To evaluate at-home opioid and benzodiazepine use, the degrees of pain and anxiety, and the incidence of probable withdrawal in post-discharge Trauma Intensive Care Unit (TICU) survivors. Methods: This was an exploratory study of post-TICU survivors who had participated in a previous study of opioid and benzodiazepine withdrawal. We surveyed survivors by telephone asking for retrospective information (during their first 4-months postdischarge- Time 1) and current information (around 2-years post-discharge- Time 2). Results: A mostly male (82%), young (median 38 years [IQR, 28−52]) sample of 27 TICU survivors reported using opioids (56%) at Time 1 for a median of 30 (IQR,14−90) days. Twelve percent of 26 survivors were still using opioids at Time 2. Sixty percent of the survivors had pain during Time 1, a median pain score of 6 (IQR, 5−8) on a 0-10 numeric rating scale (NRS).; 57% had pain at Time 2, median NRS score=6 (IQR, 4−7). Sixty-five percent of survivors had anxiety during Time 1, NRS median=7 (IQR, 5−9); 50% had anxiety at Time 2, NRS median= 6 (IQR, 3−7). At Time 1, 26% used prescribed benzodiazepines, and 12% used benzodiazepines at Time 2. Five and one of the 27 patients reported symptoms of opioid or benzodiazepine withdrawal, respectively, upon discontinuation or weaning. Conclusion: Many TICU survivors had discontinued opioid/benzodiazepine prescriptions by 4-months post discharge while half reporting pain/anxiety for up to 2-years. Investigating the effects of acute-to-chronic pain in ICU survivors and gaining a better understanding of the mechanisms of prolonged opioid use are warranted.